2010
DOI: 10.1016/j.ijnurstu.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and patient activities and interaction on psychiatric inpatients wards: A literature review

Abstract: Background-Despite major developments in community mental health services, inpatient care remains an important yet costly part of the service system and patients who are admitted frequently spend a long period of time in hospital. It is, therefore, crucial to have a good understanding of activities that take place on inpatient wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 20 publications
(45 reference statements)
4
97
2
3
Order By: Relevance
“…This includes aspects of enthusiasm, daily social activities and group spirit. Several studies have investigated involvement and patient activity in psychiatric settings (Sharac, McCrone, Sabes-Figuera, Csipke, Wood et al, 2010). One study found that reducing the formal observations on an acute psychiatric ward and introducing a structured program of individualized activity for patients led to a reduction in, for example, self-harm and violence and an increase in patient-reported quality of care, as well as a reduction in staff sickness (Dodds & Bowles, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This includes aspects of enthusiasm, daily social activities and group spirit. Several studies have investigated involvement and patient activity in psychiatric settings (Sharac, McCrone, Sabes-Figuera, Csipke, Wood et al, 2010). One study found that reducing the formal observations on an acute psychiatric ward and introducing a structured program of individualized activity for patients led to a reduction in, for example, self-harm and violence and an increase in patient-reported quality of care, as well as a reduction in staff sickness (Dodds & Bowles, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…115 There have been several reports over many years of low levels of nurse-patient interaction occurring on acute psychiatric wards. The amount of time spent as a proportion of available nursing time to interact with patients is as low as 4%, 128 with a recent review 129 concluding that patients spend substantial time apart from staff and that little time is spent delivering therapeutic activities.…”
Section: Staff Timementioning
confidence: 99%
“…The vital role of mental health nurses in establishing good therapeutic relationships with patients through highly-skilled talking, listening and empathising is wellestablished (McAndrew et al, 2014). However, a recent review of 13 studies of nursing and patient activities concluded that very little nursing time is spent delivering therapeutic interventions and may even be reducing over time (Sharac et al, 2010). Why might this be?…”
Section: "There Are Two Sorts Of 'Boring' On the Ward One Is Caused mentioning
confidence: 99%